1992
DOI: 10.1515/mult.1992.11.4.355
|View full text |Cite
|
Sign up to set email alerts
|

Panjabi/English language alternation in the early school years

Abstract: This paper describes the language alternation patterns of two groups of Panjabi/English speaking bilingual children, aged respectiveiy 3;00-3;06 and 4;00-^;06. A substantial corpus of data collected in four situational contexts in a schoolroom setting is examined by means of quantitative and qualitative procedures, and utterance-internal and sequential types of analysis. The suitability of a number of different models for uns type of child-language data is discussed and evaluated, and an analytic framework is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

1992
1992
2015
2015

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 7 publications
1
8
0
Order By: Relevance
“…This questionnaire study confirmed the chief findings listed above, revealing the same sharp disjunction between the generations; for example, 24% of the 'children' generation cohort report themselves to be monolingual English speakers, while none were monolingual in Chinese. Although this general pattern of generational difference seems to be common in migrant communities, it is not clear haw far details vary between communities; for example, it is less clearly evident in the Tyneside Panjabispeaking community (see Moffatt and Milroy 1992). The general social explanation which we are offering is based on the types of network contacts made by the children, which involve non-Chinese people much more than their parents' contacts.…”
Section: Network Structure and Language Choice In The British-born Gementioning
confidence: 73%
See 1 more Smart Citation
“…This questionnaire study confirmed the chief findings listed above, revealing the same sharp disjunction between the generations; for example, 24% of the 'children' generation cohort report themselves to be monolingual English speakers, while none were monolingual in Chinese. Although this general pattern of generational difference seems to be common in migrant communities, it is not clear haw far details vary between communities; for example, it is less clearly evident in the Tyneside Panjabispeaking community (see Moffatt and Milroy 1992). The general social explanation which we are offering is based on the types of network contacts made by the children, which involve non-Chinese people much more than their parents' contacts.…”
Section: Network Structure and Language Choice In The British-born Gementioning
confidence: 73%
“…This is true whether we are looking at maintenahce in opposition to the publically legitimised code of a stigmatised urban vernacular as in Belfast, or maintenance of an ethnic language. Migrant and other communities are not all equally successful in maintaining their community languages, and they also apparently vary in their intergenerational coininunication practices; for example the Panjabi and Bengali speakers in Newcastle do not sfem to be experiencing such a sharp intergenerational disj'unetion as the Chinese community (Moffatt and Milroy 1992). We shall argue that network analysis can illuminate the social dynamics involved in this kind of inter-group difference.…”
Section: Introductionmentioning
confidence: 96%
“…As Moffatt & Milroy (1992) have pointed out, in communities where the typical language use of adults has not been extensively researched, disentangling features of adult-like bilingual language use from developmental features of monolingual codes and of codeswitching is not straightforward. In the present study, in common with Pert & Letts (2006), the children's codeswitched utterances were found generally to be more grammatically complex (as measured by MLU) than their non-codeswitched utterances.…”
Section: Discussionmentioning
confidence: 99%
“…Narratives were elicited at school. Several researchers (Moffatt & Milroy, 1992;McClure, 1981;Martin et al, 2003) discuss the possible sociolinguistic influence of English-speaking researchers and environments on the nature of children's language production. A female Panjabi-English bilingual RA was recruited from the local community, in order to maximise the chances of eliciting Panjabi-only or Panjabi-English codeswitched utterances from the children in the predominantly English-speaking environment of school.…”
Section: Taskmentioning
confidence: 99%
“…This allowed her to collect a tape-recorded corpus of spontaneous speech and to observe children's language choice and language mixing patterns without imposing her presence as a researcher. Such participant observation procedures allow observation of classroom participants with minimum observer effect (Milroy, 1987; see also Moffatt and Milroy (1992) for a report of a similar study of a group of bilingual children at school). Based upon Mrs. Kim's evaluations of students' language pro®ciency, the 12 Korean students were organized as six pairs such that members of each pair showed comparable pro®ciency in both English and Korean, as shown in Table 2.…”
Section: Elicitation Procedures For Spontaneous Speechmentioning
confidence: 99%